Application of Nanoparticles in Diagnosis and Treatment of Pancreatic Cancer. (6th June 2022) - Yuan, Juzheng; Wang, Yang; Cao, Yang; Yue, Shuqiang; Li, Xiao
Abstract : Objective . In order to study the application of nanoparticles in the diagnosis and treatment of pancreatic cancer, we retrospectively analyzed pancreatic cancer patients after operation. Method . 60 cases of pancreatic cancer and surgical treatment were selected from our hospital. The time ranged from March 2018 to March 2019. The age ranged from 27 to 81 years. There were 36 males and 24 females, with an average age of 46.23 (7.63) years. Among them, the observation group consisted of nanotube artificial tubes, 16 males and 14 females, while the control group adopted nylon tube, male 18 and female 12. The patient was diagnosed by abdominal CT, and the patient's demographic data and basic clinical data were recorded at the same time. Result . In this study, 60 patients were divided into groups and compared. The patients underwent surgical resection of pancreaticoduodenum and reconstruction of pancreaticoduodenal papillary duct. Among them, the observation group used nanocomposite artificial tube, while the observation group used nanocomposite artificial tube and placed drainage tube to drain the peritoneal effusion to prevent the effusion from forming in abdominal hypertension and infection. The amount of postoperative bleeding, operation time, and postoperative concomitant symptoms were observed, and the differences between the two materials were analyzed. Conclusion . The reconstruction of pancreaticoduodenal papillary duct with nanomaterials has certain advantages for postoperative recovery, reduces postoperative complications, reduces the probability of infection, and improves the therapeutic effect.